Empirical test of low self-control theory using post-treatment substance use and recidivism outcomes of parolees participating in an experimental intervention? - Chintakrindi, Sriram (Criminology, criminal justice, law & society, 2015)
This study tests Gottfredson and Hirschi’s (1990) low self-control theory using secondary-data from parolees who participated in an experimental intervention called the Step’n Out study (Friedmann et al., 2008). This study hypothesizes that parolees with low self-control will have increased odds of engaging in post-treatment substance use and recidivism outcomes at the 3- and 9-month follow-up periods. The relationship between self-control and the post-treatment outcomes will be analyzed using Independent Samples t-tests, logistic regression models, and Confirmatory Factor Analysis. Bivariate results indicate that parolees who had self-reported physically or verbally threatening someone at the follow-up periods had statistically significantly lower self-control means compared to parolees who did not self-report physically or verbally threatening behaviors(p< 0.05). The results from the logistic regression analysis reveal that parolees with low levels of self-control have statistically significant increased odds of engaging in physically or verbally threatening behavior compared to parolees who did not report those behaviors at the 3-month follow-up period (p< 0.05). Generally, using the exploratory multivariate analytical approach, low self-control theory was not found to be a strong theoretical predictor of substance use and recidivism outcomes for parolees in the study. We did find that parolees randomly assigned to the experimental intervention had decreased odds of engaging in threatening behaviors. However, we did not observe that the treatment intervention moderated the relationship between low self-control and post-treatment outcomes. The results from the Confirmatory Factor Analysis reveal that low self-control theory is a weak predictor of total deviance.